From GSM to LTE-Advanced : an Introduction to Mobile Networks and Mobile Broadband. - Sauter, Martin (Wiley, 2014)
This revised edition contains not only a technical description of the different wireless systems available today, but also explains the rationale behind the different mechanisms and implementations; not only the 'how' but also the 'why'. Therefore the advantages and also limitations of each technology become apparent. Offering a solid introduction to major global wireless standards and comparisons of the different wireless technologies and their applications, this edition has been updated to provide the latest directions and activities in 3GPP standardization up to Release 12, and importan.